Addressing reflectivity losses in multi-junction solar cells to achieve 50% power conversion efficiency. (10th November 2015) - Wilson, T.; Thomas, T.; Führer, M.; Ekins-Daukes, N. J.
Abstract : As we progress towards the next generation of multi-junction solar cell technology, incorporating four junctions or more, current dual-layer coating technology applied to commercially available triple-junction solar cells will become inadequate as the current matching between the lower sub cells, absorbing in the infrared, becomes more critical. Here we present some single, double and triple layer anti-reflection coatings for comparison, optimised using a genetic algorithm, for both triple- and quad-junction solar cell architectures. It is found that there is a small increase in power conversion efficiency between the dual and triple layer coatings applied to the triple-junction structure (0.7%), however this is more than doubled when optimised dual and triple layer coatings are applied to the quad-junction device (1.5%). This work demonstrates the effectiveness of a well-optimised multi-layer anti-reflection coating in realising an appreciable increase in device performance in the next generation of multi-junction solar cells, highlighting a realistic power conversion efficiency of up to 50.35%.